Factors Determining the Dynamics of Physical Fitness and Physical Development of Schoolchildren in the Soviet Period and at the Present Stage (Journal of Educational Sciences, 2026)
The article presents the results of the analysis of physical fitness and physical development of 9th grade schoolchildren in the Soviet period and at the present stage. The purpose of the study is to investigate the characteristics of physical development and physical fitness of 9th grade schoolchildren during the study period, the factors that determine them, and suggest ways to improve them. The research areas were to determine the specifics of the level of physical development and physical fitness of 9th grade schoolchildren; the opinions of physical education teachers regarding the dynamics of signs of physical perfection of schoolchildren; establishing a correlational relationship between the studied characteristics; developing improvements in the physical development and physical fitness of 9th-grade schoolchildren. The obtained results improve theoretical understanding of the factors characterizing the dynamics of physical fitness and physical development of schoolchildren. And the practical results provide methodological approaches for implementing the development of these signs of physical perfection. The study involved 40 physical education teachers and 300 ninth-grade students in Aktobe. It was found that today’s schoolchildren are inferior to their Soviet-era peers in terms of physical fitness. This was particularly true for indicators characterizing students’ speed and speed-strength abilities. It was found that the height and body weight of modern schoolchildren are higher than those of their Soviet-era peers. This was particularly true for indicators characterizing students’ speed and speed-strength abilities. It was found that the height and body weight of modern schoolchildren are higher than those of their Soviet-era peers. At the same time, the functional capabilities of modern schoolchildren are reduced.Keywords: schoolchildren, physical fitness, physical development, dynamics, correlation analysis, factors.